A review on antimicrobial activity of mushroom (Basidiomycetes) extracts and isolated compounds - Alves, Maria José (2012)
Despite the huge diversity of antibacterial compounds, bacterial resistance to first choice antibiotics has been drastically increasing. Moreover, the association between multi-resistant microorganisms and nosocomial infections highlight the problem, and the urgent need for solutions. Natural resources have been exploited in the last years and among them mushrooms could be an alternative as source of new antimicrobials. In this review we present an overview about the antimicrobial properties of mushroom extracts, highlight some of the active compounds identified including low and high molecular weight (LMW and HMW, respectively) compounds. LMW compounds are mainly secondary metabolites, such as sesquiterpenes and other terpenes, steroids, anthraquinones, benzoic acid derivatives, and quinolines, but also primary metabolites such as oxalic acid. HMW compounds are mainly peptides and proteins. Data available from literature indicate a higher antimicrobial activity of mushroom extracts against Gram-positive bacteria. Among all the mushrooms, Lentinus edodes is the most studied species and seems to have a broad antimicrobial action against both Gram-postive and Gram-negative bacteria. Plectasin peptide, obtained from Pseudoplectania nigrella, is the isolated compound with highest antimicrobial activity against Gram-positive bacteria, while 2-aminoquinoline, isolated from Leucopaxillus albissimus, presents the highest antimicrobial activity against Gram-negative bacteria.